2020
DOI: 10.3389/fspas.2020.00025
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Plasma Flows at Granular and Supergranular Scales With a New Architecture for the DeepVel Neural Network

Abstract: The wealth of observational data available has been instrumental in investigating physical features relevant to solar granulation, supergranulation and Active Regions. Meanwhile, numerical models have attempted to bridge the gap between the physics of the solar interior and such observations. However, there are relevant physical quantities that can be modeled but that cannot be directly measured and must be inferred. For example, direct measurements of plasma motions at the photosphere are limited to the line-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…where v and v 0 represent the estimated and simulated horizontal velocity vectors, respectively. This definition is consistent withTremblay & Attie (2020) andTremblay et al (2021b). This dot product indicates the difference of the orientation of the vectors.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…where v and v 0 represent the estimated and simulated horizontal velocity vectors, respectively. This definition is consistent withTremblay & Attie (2020) andTremblay et al (2021b). This dot product indicates the difference of the orientation of the vectors.…”
supporting
confidence: 90%
“…The results of DeepVel and LCT are similar when they are averaged, however, DeepVel still has the advantage of reproducing the kinetic power spectra on sub-supergranule scales. Tremblay & Attie (2020) developed a new architecture for DeepVel using the U-NET architecture and found that it is more effective than other tracking methods. However, their accuracies were not verified at various spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…but also scales up the size of the sub-images presented during training (DeepVelU: Tremblay and Attie, 2020;Tremblay et al, 2019). Our recent efforts have also focused on modifying the inputs of the neural network in order to accept a combination of consecutive intensitygrams (i.e., the default inputs), magnetograms and Dopplergrams (Tremblay and Attie, 2020). This is motivated by the magnetic induction equation which relates transverse plasma motions to the magnetic field and line-of-sight plasma motions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of DeepVel and LCT are similar when they are averaged; however, DeepVel still has the advantage of reproducing the kinetic power spectra on sub-supergranule scales. Tremblay & Attie (2020) developed a new architecture for DeepVel using the U-NET architecture and found that it is more effective than other tracking methods. However, their accuracies have not been verified at various spatial scales.…”
Section: Introductionmentioning
confidence: 99%